The London Olympic Games 2012: Points of interest for the development of elite sport in Australia - Wilson, G. (Journal of Australian Strength and Conditioning, 2012)
The London Olympic Games were a remarkable event that captured the world`s attentions and further strengthened the Olympic Movement on the international stage. Full credit should be afforded to the organisers of the London Games and to the outstanding performance of the team from Great Britain who exceeded all expectations. The Australian team won 7 gold medals and placed 10th on the overall medal tally which was well down on the top 5 place that was targeted by the Australian Olympic Committee and was Australia`s worst performance at an Olympic Games since 1992. The purpose of this article is to discuss some of the reasons underlying Australia`s poor performance with a view to achieving a better result at future Olympic Games. Further, some of the unique aspects of the results achieved by athletes at the London Olympics will be reviewed with the intention of examining implications for the strength and conditioning field more generally.